Electrophysiological Properties of Induced Pluripotent Stem Cell-Derived Midbrain Dopaminergic Neurons Correlate With Expression of Tyrosine Hydroxylase - Rakovic, Aleksandar; Voß, Dorothea; Vulinovic, Franca; Meier, Britta; Hellberg, Ann-Katrin; Nau, Carla; Klein, Christine; Leipold, Enrico (Frontiers in Cellular Neuroscience, 2022)
Induced pluripotent stem cell (iPSC)-based generation of tyrosine hydroxylase-positive (TH+) dopaminergic neurons (DNs) is a powerful method for creating patient-specific in vitro models to elucidate mechanisms underlying Parkinson’s disease (PD) at the cellular and molecular level and to perform drug screening. However, currently available differentiation paradigms result in highly heterogeneous cell populations, often yielding a disappointing fraction (<50%) of the PD-relevant TH+ DNs. To facilitate the targeted analysis of this cell population and to characterize their electrophysiological properties, we employed CRISPR/Cas9 technology and generated an mCherry-based human TH reporter iPSC line. Subsequently, reporter iPSCs were subjected to dopaminergic differentiation using either a ‘floor plate protocol’ generating DNs directly from iPSCs or an alternative method involving iPSC-derived neuronal precursors (NPC-derived DNs). To identify the strategy with the highest conversion efficiency to mature neurons, both cultures were examined for a period of eight weeks after triggering neuronal differentiation by means of immunochemistry and single-cell electrophysiology. We confirmed that mCherry expression correlated with the expression of endogenous TH and that genetic editing did neither affect the differentiation process nor the endogenous TH expression in iPSC- and NPC-derived DNs. Although both cultures yielded identical proportions of TH+ cells (30%), whole-cell patch-clamp experiments revealed that iPSC-derived DNs gave rise to larger currents mediated by voltage-gated sodium and potassium channels, showed a higher degree of synaptic activity, and fired trains of mature spontaneous action potentials more frequently compared to NPC-derived DNs already after two weeks in differentiation. Moreover, spontaneous action potential firing was more frequently detected in TH+ neurons compared to the TH cells, providing direct evidence that these two neuronal subpopulations exhibit different intrinsic electrophysiological properties. In summary, the data reveal substantial differences in the electrophysiological properties of iPSC-derived TH+ and TH neuronal cell populations and that the ‘floor plate protocol’ is particularly efficient in generating electrophysiologically mature TH+ DNs, which are the most vulnerable neuronal subtype in PD.